2021
DOI: 10.1002/cam4.3918
|View full text |Cite
|
Sign up to set email alerts
|

Patient–provider discussion about emotional and social needs, mental health outcomes, and benefit finding among U.S. Adults living with cancer

Abstract: Background A discussion about patient's nonmedical needs during treatment is considered a crucial component of high‐quality patient–provider communication. We examined whether having a patient–provider discussion about cancer patients’ emotional and social needs is associated with their psychological well‐being. Methods Using the 2016–2017 Medical Expenditure Panel Survey‐Experiences with Cancer Survivorship Supplement (MEPS–ECSS) data, we identified the cancer survivors in the United States (US) who reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…Real-world data, defined as data related to patient health status and/or care that are collected from a variety of sources, play a key role regarding how health and health care work in real-life settings [ 23 ]. There was one real-world data study that investigated the effect of patient–physician communication focusing on mental and emotional health, and it found that cancer survivors who had a conversation about emotional and social needs were at lower odds of having depression symptoms compared to those who did not [ 24 ]. Since we are interested in how certain aspects of patient–physician communication affect mental health on cancer patients, in this study we aimed to analyze the association between patient–physician communication and self-reported mental health status using real-world data.…”
Section: Introductionmentioning
confidence: 99%
“…Real-world data, defined as data related to patient health status and/or care that are collected from a variety of sources, play a key role regarding how health and health care work in real-life settings [ 23 ]. There was one real-world data study that investigated the effect of patient–physician communication focusing on mental and emotional health, and it found that cancer survivors who had a conversation about emotional and social needs were at lower odds of having depression symptoms compared to those who did not [ 24 ]. Since we are interested in how certain aspects of patient–physician communication affect mental health on cancer patients, in this study we aimed to analyze the association between patient–physician communication and self-reported mental health status using real-world data.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, as the time since diagnosis increased and survival needs seemed more assured, family units were increasingly likely to unite under a shared benefit-finding process. A recent study with cancer survivors (Hong et al, 2021) suggests that salutogenic (well-being focused) psychoeducation may help to advantageously hasten this process. The study (Hong et al, 2021) found that although only 33.6% of patients discussed emotional and social survival needs with their health care provider, having such conversations was associated with 45% less likelihood of suffering depressive symptoms, odds ratio (OR): 0.45; 95% confidence interval (CI): [0.26, 0.77], p = 0.004, and a substantial 97% increased likelihood of acknowledging positive changes through benefit-finding, OR: 1.97; 95% CI: [1.46, 2.66], p < 0.0001.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study with cancer survivors (Hong et al, 2021) suggests that salutogenic (well-being focused) psychoeducation may help to advantageously hasten this process. The study (Hong et al, 2021) found that although only 33.6% of patients discussed emotional and social survival needs with their health care provider, having such conversations was associated with 45% less likelihood of suffering depressive symptoms, odds ratio (OR): 0.45; 95% confidence interval (CI): [0.26, 0.77], p = 0.004, and a substantial 97% increased likelihood of acknowledging positive changes through benefit-finding, OR: 1.97; 95% CI: [1.46, 2.66], p < 0.0001. Future research may examine benefit-finding processes in the short term following diagnosis to determine the optimal timing of benefit-finding training post-diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast discussions of acceptance, hope, and stoicism were often far more positive and implied better coping. Moreover, sentiments of hope (Olsson et al, 2011), resilience (Eicher et al, 2015), and benefit finding (Hong et al, 2021; Lin et al, 2021) have been shown to help people live with advanced forms of cancer, whereas denial is linked to poorer psychological outcomes (Nipp et al, 2016; Thompson et al, 2009), and may deter more adaptive forms of coping that inspire growth and psycho-emotional development (Vos & de Haes, 2007). Consequently, while individuals used various strategies across the literature to augment their well-being, these did not always appear equal, and efforts to cope whether through acceptance, hope, and/or stoicism, appeared far more beneficial to their long-term happiness.…”
Section: Discussionmentioning
confidence: 99%